Effect of Extraction Methods on Chemical Constituents and Antioxidant Activity of Essential Oil from Thymus vulgaris L. - Huan LIU; Jutang ZHAO; Haitao LUO; Zhouying REN; Dengyin SHAO (Shipin gongye ke-ji, 2022)
The essential oils from Thymus vulgaris L. were extracted by using different methods of stream distillation (SD), simultaneous distillation extraction (SDE), and cold plasma assisted extraction (CPAE) separately，then the volatile components in the essential oils were identified by GC-MS. The contents of total phenols, flavonoids and anthocyanins in essential oil were determined. Its antioxidant activity in vitro was evaluated by three antioxidant indexes: DPPH•, ABTS+• and total antioxidant capacity, and the correlation between the main active components in essential oil and antioxidant capacity was analyzed. Therefore, the extraction method with higher rate and better antioxidant capacity was obtained. The results showed that different extraction methods had significant difference in yield (P<0.05). And the SDE method had the highest yield, reaching 1.30%. By GC-MS analysis, 36 components of the three essential oils were detected. The main volatile components were borneol (32.194%~32.515%), carvacrol (17.265%~19.998%), thymol (13.031%%~15.202%), α-terpinol (11.296%~12.012%). The SDE and CPAE methods had higher contents of main active ingredients than SD method. In the determination results of total phenols, total flavonoids and anthocyanins, the contents of total phenols and anthocyanins in the essential oil prepared by SDE method were 133.67±0.20 mg GA/g EO and 0.32±0.02 mg/g EO, respectively. The contents of total flavonoids in the essential oil prepared by CPAE method were the highest, reaching 54.82 mg Rutin/g EO. In vitro antioxidant experiments, the three essential oils showed strong antioxidant activity and obvious dose-effect relationship to various antioxidant indexes within the experimental concentration range. Among them, the essential oil obtained by SDE method had better scavenging effect on free radicals, and the scavenging rate was above 96% at the highest experimental concentration. Correlation analysis showed that the antioxidant activity of the essential oils were closely related to the content of phenols and other main substances. In conclusion, according to the experimental results, the SDE method is a more desirable method for the extraction of essential oils from Thymus vulgaris L..